Profiling internal forced migrants in north-eastern Nigeria / Sadiq Mukhtar, Rosniza Aznie Che Rose and Lam Kuok Choy - Mukhtar, Sadiq; Che Rose, Rosniza Aznie; Lam, Kuok Choy (Research Management Centre (RMC), 2020)
The objective of this paper is to characterise internal forced migrants displaced in North Eastern part of Nigeria as the result of conflicts, and natural disasters. It was estimated that nearly 1.8 million out of the total of more than 2.1 million internally displaced people in Nigeria dwell in this region. Data obtained from the United Nations International Organisation for Migration (IOM, Nigeria), was used to attain the research’s goal using Geo-Information techniques (GIS analysis) and statistical analysis. Results revealed that 55 percent of internally displaced people are female while 45 percent are male; it also revealed that 60 percent of IDPs in Northeast Nigeria are dwelling in host communities, while the remaining 40 percent are found in formal and informal camps. The study also revealed that 99.9 percent of the migrants flee because of conflicts and communal clashes, while 0.1 percent escape due to natural disaster. It further revealed that the majority of IDPs were displaced in the year 2015 due to an increase in the number of conflicts and insurgent activities in the region. Finally, this research found that Borno state has the highest number of IDPs, formal and informal camps, and host community settlements.